Theoretical Study of a Pneumatic Device for Precise Application of Mineral Fertilizers by an Agro-Robot - Lillerand, Tormi; Liivapuu, Olga; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Olt, Jüri (My University, 2025)
This article presents the development of a new pneumatic device for the precise applicationof mineral fertilizers, designed for use in precision agriculture systems involving farming robots. The proposed device is mounted on an autonomous agricultural platform andutilizes a machine vision system to determine plant coordinates. Its operating principle is based on accumulating a single dose of fertilizer in a chamber and delivering it preciselyto the plant’s root zone using a directed airflow. The study includes a theoretical inves tigation of fertilizer movement inside the applicator tube under the influence of airflow and rotational motion of the tube. A mathematical model has been developed to describe both the relative and translational motion of the fertilizer. The equations, which account for frictional forces, inertia, and air pressure, enable the determination of optimal struc tural and kinematic parameters of the device depending on operating conditions and the properties of the applied material. The use of numerical methods to solve the developed mathematical model allows for synchronization of the device’s operating time parameters with the movement of the agricultural robot along the crop rows.
Keywords: precision agriculture; technological materials; pneumatic transport; farming robot; parameters; pressure; time